2022
DOI: 10.1002/jmd2.12294
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional natural history study of aspartylglucosaminuria

Abstract: Aspartylglucosaminuria (AGU) is a rare lysosomal storage disorder that causes stagnation of development in adolescence and neurodegeneration in early adulthood. Precision therapies, including gene transfer therapy, are in development with a goal of taking advantage of the slow clinical course. Understanding of disease natural history and identification of disease‐relevant biomarkers are important steps in clinical trial readiness. We describe the clinical features of a diverse population of patients with AGU, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Conventional magnetic resonance imaging (MRI) studies in AGU have shown brain atrophy, delayed myelination, decreased thalamic T2 signal intensity, and increased T2 signal intensity in the periventricular white matter [12][13][14][15][16] . In addition, based on a visual analysis, poor differentiation between white and gray matter, thinning of corpus callosum, cerebellar atrophy, and mild ventricular dilatation have been reported 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional magnetic resonance imaging (MRI) studies in AGU have shown brain atrophy, delayed myelination, decreased thalamic T2 signal intensity, and increased T2 signal intensity in the periventricular white matter [12][13][14][15][16] . In addition, based on a visual analysis, poor differentiation between white and gray matter, thinning of corpus callosum, cerebellar atrophy, and mild ventricular dilatation have been reported 14 .…”
Section: Introductionmentioning
confidence: 99%